Effects of milling/estate practices on OER (Sime Darby`s experiences) - Keu Haw Gee (Palm Oil Research Institute of Malaysia (PORIM), 2014)
It is recognized that palm oil is be made in the field as the content of oil cannot be enhaced beyond what is inherent in the fruit bunches. Much can be done by the estate and CPO mills in maximizing product recovery while striving to keep field processing losses to the minimum. In our effort to achieve optimum product recovery and high quality product, there should be a strong interaction and implementation of the various fundamental facts which will be the subject for presentation.